A PENGARUH BUDAYA KERJA ORGANISASI TERHADAP DISIPLIN APARATUR SIPIL NEGARA DI DINAS PERTANIAN PROVINSI BANTEN - Dedi Wahyudin (Jurnal Kebijakan Pembangunan Daerah, 2025)
The background of this study highlights a significant gap between the strict formal regulations of Government Regulation Number 94 of 2021 and the reality of high levels of indiscipline at the Department of Agriculture of Banten Province, manifested in issues such as tardiness and low accountability in task completion. This study aims to empirically demonstrate the influence of organizational work culture as a primary determinant of State Civil Apparatus (ASN) discipline. Employing an explanatory quantitative method, the study involved 100 ASN respondents selected via purposive sampling. Data analysis was conducted using simple linear regression. The results reveal that organizational work culture contributes a positive and significant influence of 56% to the variance in work discipline ($R^2 = 0.56$), while the remaining 44% is influenced by other factors. A crucial finding of this study confirms that work culture functions effectively as a "soft control" mechanism capable of fostering voluntary compliance and professional ethics, surpassing the effectiveness of mere external supervision. Practically, this study advocates shifting away from punitive management patterns that rely solely on sanctions, moving instead toward a more humanistic "Culture Based Management" approach. Leadership role modeling is recommended as a pivotal element of bureaucratic reform, transforming fear driven compliance into consciousness driven discipline, to realize excellent and accountable public service.